Thermoelectric properties of indium doped Cu2CdSnSe4. (May 2016) - Chetty, Raju; Bali, Ashoka; Mallik, Ramesh Chandra
Abstract: Recently, research in copper-based quaternary chalcogenide materials has been found to be interesting for the study of thermoelectric properties because of their low thermal conductivity due to complex crystal structures. In the present work, stoichiometric quaternary chalcogenide compounds Cu2 CdSn1-x Inx Se4 (x = 0, 0.025, 0.05, 0.1) were prepared by solid state synthesis. The powder X-ray diffraction patterns of all the samples showed a tetragonal crystal structure with the space group I 4 ¯ 2m of the main phase. In addition to this phase, a small amount of impurity phase CdSe was present in all the samples, as confirmed by Rietveld analysis. The elemental composition of all the samples characterized by an Electron Probe Micro Analyzer showed a slight deviation from the nominal composition. The transport properties were measured in the temperature range of 350 K–723 K. The positive Seebeck coefficient of all the compounds indicate that the majority carriers are holes. The Seebeck coefficient and electrical resistivity did not follow the trend in the expected manner with In doping, which could be influenced by the presence of the impurity phases. The total thermal conductivity of all the samples was dominated by the lattice thermal conductivity, while the electronic contribution was very small due to the low carrier contribution. A lattice thermal conductivity decrease with an increase of temperature indicates the dominance of phonon–phonon scattering at higher temperatures. The maximum figure of merit z T = 0.30 at 723 K was obtained for the compound Cu2 CdSn0.9 In0.1 Se4 . Highlights: Thermoelectric properties of quaternary chalcogenide compounds have been studied. Cu2 CdSnSe4 crystallised in stannite structure along with trace amount of CdSe. Transport properties affected by carrier concentration change and impurity phases. Maximum thermoelectric zT = 0.30 at 723 K obtained for Cu2 CdSn0.9 In0.1 Se4 .